A study on the factors that lead to job stress among nurses at Malacca General Hospital / Ariff Hanafi Omar and Mohammad Noor Izwan Hussin - Omar, Ariff Hanafi; Hussin, Mohammad Noor Izwan (Faculty of Administrative Science and Policy Studies, 2014)
Stress is an emotional feeling that and body reaction that totally change people’s mood and behavior toward his/her surrounding. Stress can be good or bad. Every person in the whole world cannot run from feeling stress in certain situation. Stress generally can be felt not only during work or in working environment, but also be felt in relationship, in financial institution, and others. Stress could be beneficial if one could handle it positively because it might motivate the person to overcome his/her problem. Plus, in fact everyone needs stress in their lives because without stress the life of a person would be gloomy and uninteresting.